2022
DOI: 10.3390/toxins14070433
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Kinetic Models for Pore Formation of Bacillus thuringiensis Cry Toxin

Abstract: Cry proteins from Bacillus thuringiensis (Bt) and other bacteria are pesticidal pore-forming toxins. Since 2010, when the ABC transporter C2 (ABCC2) was identified as a Cry1Ac protein resistant gene, our understanding of the mode of action of Cry protein has progressed substantially. ABCC2 mediates high Cry1A toxicity because of its high activity for helping pore formation. With the discovery of ABCC2, the classical killing model based on pore formation and osmotic lysis became nearly conclusive. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 88 publications
(187 reference statements)
1
22
0
Order By: Relevance
“…All four Bt strains potently killed their specific target insects, in which BtA was the most virulent strain against S. exigua . This virulence specificity was likely to be a specific interaction between Cry toxin and its binding site(s) in the target insect [ 41 ]. When Bt spores are consumed by the target insects, Cry toxins associated with spores are released in the midgut lumen and cleaved by insect digestive enzymes to become active, protease-insensitive toxin proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All four Bt strains potently killed their specific target insects, in which BtA was the most virulent strain against S. exigua . This virulence specificity was likely to be a specific interaction between Cry toxin and its binding site(s) in the target insect [ 41 ]. When Bt spores are consumed by the target insects, Cry toxins associated with spores are released in the midgut lumen and cleaved by insect digestive enzymes to become active, protease-insensitive toxin proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, it did not effectively control other insects. This differential toxicity of BtA+XhE might be due to a specific interaction between Bt Cry toxins and their binding site(s) on the gut epithelium of the target insects [ 41 ]. Thus, replacing BtA in the IBC agent with other Bt strains might control other insect species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are rather different from other studies reported previously for lepidopteran-specific Cry1A toxins that pre-binding of the toxin to cadherin-like receptors seems to be critically needed for toxin oligomerization before interacting with second membrane-bound receptors (e.g., mALPs or mAPNs) for membrane insertion and pore formation [ 7 , 55 ]. However, it has been recently claimed that the completion of the oligomeric assembly of Cry1A-ABCC2 receptor complexes could directly signify membrane insertion and pore formation without the pre-binding to cadherin receptors [ 56 ]; it is noteworthy from the cytotoxicity studies that the Cq -mALP1264-expressed Sf 9 cells were found to be much more susceptible to Cry4Aa than Cry4Ba; these in vitro cytotoxic effects are thus in good agreement with our previous biotoxicity findings that Cry4Aa is much more active than Cry4Ba against Culex larvae [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plausible 3D modeled structures of Cq -mALPs were constructed based on the target-template alignment with the shrimp-ALP high-resolution (1.9Å) crystal structure (PDB: 1K7H) [ 56 ] via Phyre2 ( (accessed on 12 September 2022)) and displayed by UCSF Chimera ( chimera/ (accessed on 12 September 2022)). The local quality of both modeled structures was validated by VERIFY-3D [ 59 ] and their stereochemistry was analyzed using the Psi/Phi Ramachandran plot computed with PROCHECK [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the genetic basis of resistance can be useful for monitoring, managing, and countering pest resistance to Bt crops [ 15 , 16 , 17 , 18 ]. To facilitate development of effective resistance management strategies, scientists have determined the genetic basis of resistance to Bt toxins in many lab-selected strains, including strains derived from susceptible populations by either mass selection or selection of families generated for F 1 or F 2 screens [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. If lab-selected resistance and field-selected practical resistance have a similar genetic basis, the lab results can be useful for designing and proactively implementing strategies to delay resistance in the field [ 27 ].…”
Section: Introductionmentioning
confidence: 99%